2015
DOI: 10.1007/s10549-015-3595-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic polyphenol intake and breast cancer survival: the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort

Abstract: The aim was to investigate the association between pre-diagnostic intakes of polyphenol classes (flavonoids, lignans, phenolic acids, stilbenes, and other polyphenols) in relation to breast cancer survival (all-cause and breast cancer-specific mortality). We used data from the European Prospective Investigation into Cancer and Nutrition cohort. Pre-diagnostic usual diet was assessed using dietary questionnaires, and polyphenol intakes were estimated using the Phenol-Explorer database. We followed 11,782 breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 39 publications
(56 reference statements)
2
46
0
Order By: Relevance
“…Except for the sugarcane vinegar (Mimura and others ), research on the anticancer activities of fruit vinegars has not yet been published. Nevertheless, according to investigations on the anticancer activities of polyphenols (such as resveratrol) in some fruits (Shukla and Singh ; Peng and others ; Kyrø and others ; Zamora‐Ros and others ), the long‐term intake of fruit vinegars may have a positive anticancer effect in humans as well.…”
Section: Functional Properties Of Vinegarsmentioning
confidence: 99%
“…Except for the sugarcane vinegar (Mimura and others ), research on the anticancer activities of fruit vinegars has not yet been published. Nevertheless, according to investigations on the anticancer activities of polyphenols (such as resveratrol) in some fruits (Shukla and Singh ; Peng and others ; Kyrø and others ; Zamora‐Ros and others ), the long‐term intake of fruit vinegars may have a positive anticancer effect in humans as well.…”
Section: Functional Properties Of Vinegarsmentioning
confidence: 99%
“…On the other hand, Feng et al [36] found a protective effect of anthocyanidins, proanthocyanidins, flavanones, flavones, flavonols and isoflavones. Some other studies found a protective effect of flavonol consumption against BC risk among none-to-low alcohol drinkers compared to heavy drinkers [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…Case-control studies carried out in USA [38], Mexico [39,40] and Greece [41] observed a lower risk of BC among postmenopausal women with a high intake of some flavonoid subclasses (i.e., flavones, flavanols, and flavonols). Nevertheless, results from prospective cohort studies indicated that the chemopreventive role of flavonoids and flavonols in BC carcinogenesis still remains unclear [18,19,42]. Other studies suggested that protective associations were stronger in premenopausal than in postmenopausal women [43,44], whereas Dong et al showed the opposite [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analysis we previously found consistent evidence for protective effects of higher lignan exposure, measured as prediagnosis estimated dietary lignan intake or pre/postdiagnosis blood ENL, for both all‐cause mortality (ACM) and breast cancer‐specific mortality (BCSM) in postmenopausal breast cancer patients . Since then, a large study confirmed the inverse association between prediagnosis lignan intake and BCSM in postmenopausal women, while another study found prediagnosis plasma ENL to be associated with reduced BCSM . However, the potential underlying biological mechanisms linking lignans to breast cancer prognosis have not yet been well elucidated.…”
Section: Introductionmentioning
confidence: 95%